Transformasi Digital Melalui Pelatihan Odoo ERP sebagai Sistem Manajemen Bisnis Terpadu - Isrofi, Nisa; Erly Ekayanti Rosyida; Rizky Fenaldo Maulana (Pusat Riset dan Inovasi Nasional, 2026)
Odoo training at PT Tamaddun Inti Perkasa aims to improve existing business processes within the company through process integration, data transparency, and operational efficiency. Odoo implementation can improve the Company's operational efficiency and also increase HR capacity through mentoring and training to acquire digital skills relevant to the development of Industry 4.0. The training was conducted through participatory practices to improve digital skills through real company data. The training stages included identifying company problems, general socialization of Odoo usage, training, mentoring, evaluation, and feedback. The training participants consisted of 9 people from several departments and was held on December 8, 2025. A pre-training questionnaire proved that the company's employees are aware of the importance of integrated data management. This training activity successfully improved digital competency through the use of Odoo and respondents agreed that using Odoo can help simplify their work. The use of a flexible integrated system according to company needs such as Odoo is one solution. The use of six modules: Manufacturing, Inventory, Sales, Purchasing, Accounting, and Point of Sales (POS) is considered very important and must be understood by the company as a starting point for further development.